Putting the crisis to work: The real estate sector and London's housing crisis. (August 2021) - Brill, Frances; Raco, Mike
Abstract: The idea of 'crisis' plays an important role in academic and policy imaginations (Heslop and Ormerod, 2020), particularly since the global financial crisis. Across major western cities, at the same time as policy-makers have had to respond to ' the (economic) crisis', many have also experienced intense 'housing crises' and the acute divergence of average incomes and house prices. In response, cities such as London have become central sites in debates around housing acquisition by the ultra-wealthy, land value extraction and growing levels of unaffordability. However, much critical geography research on housing crises is state-centred or focused on civil society impacts, with relatively little reflection on the real estate sector and the work that crisis does as a narrative in shaping institutionalised and actor-centred practices. In this paper, we draw on in-depth research with developers, investors, and advisors in London to argue that crisis-driven policy responses have created political risk which is differentially experienced by actors across the sector, with large housebuilders and advisors benefitting whilst smaller niche developers move out. Moreover, we show how consultants, investors and developers have used the crisis situation to create new geographies, products and investor types in the housing market. These, in turn, require regulatory support and demonstrate the inherently political nature of crisis narratives' use. We use the London case to broaden understandings of the impact that conceptualisations of 'crisis' have on urban and regional planning practices, and how these influence and shape processes of contemporary urban development.